2017
DOI: 10.3389/fpsyg.2017.01888
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Emotional Intelligence and Learning Strategies in Spanish University Students: A New Perspective from a Canonical Non-symmetrical Correspondence Analysis

Abstract: Recent studies have revealed that emotional competences are relevant to the student’s learning process and, more specifically, in the use of learning strategies (LSs). The aim of this study is twofold. First, we aim to analyze the relationship between perceived emotional intelligence (PEI) and LSs applying the scales TMMS-24 and Abridged ACRA to a sample of 2334 Spanish university students, whilst also exploring possible gender differences. Second, we aim to propose a methodological alternative based on the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
2
10
0
1
Order By: Relevance
“…Previous studies in other parts of the world have also shown that female students have a higher level of competence and willingness to perform better in their academic programs (DiPrete & Buchmann, 2013;Tariq et al, 2016;Quadlin, 2018). This result is also in agreement with the results obtained by Vega-Hern andez et al (2017). Furthermore, female students with "good," "very good" or "excellent" grades showed significant differences in their use of learning strategies compared to male students.…”
Section: Learning Strategies and Academic Performancesupporting
confidence: 87%
“…Previous studies in other parts of the world have also shown that female students have a higher level of competence and willingness to perform better in their academic programs (DiPrete & Buchmann, 2013;Tariq et al, 2016;Quadlin, 2018). This result is also in agreement with the results obtained by Vega-Hern andez et al (2017). Furthermore, female students with "good," "very good" or "excellent" grades showed significant differences in their use of learning strategies compared to male students.…”
Section: Learning Strategies and Academic Performancesupporting
confidence: 87%
“…Young adults have certainly experienced more negative emotions and loss of self-confidence, with a possible impact on reasoning ability, learning, memory, and concentration, for example for university performances. In fact, emotional skills are crucial to cognitive processes as they affect cognitive styles, use of learning strategies [ 44 ], and, consequently, performance [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…En otras palabras, para que un estudiante tipo mejore 1 punto en sus calificaciones necesitaría mejorar al menos en 10 aspectos distintos de sus hábitos de estudio. Para explicar esta asociación débil, nuestra hipótesis es que los hábitos de estudio son uno de muchos factores que determinan el rendimiento académico, factores que incluyen los estilos de enseñanza (Wentzel, 2002), los estilos de aprendizaje (Akhlaghi, Mirkazemi, Jafarzade, & Akhlaghi, 2018), la inteligencia (Vega-Hernández, Patino-Alonso, Cabello, Galindo -Villardón, & Fernández-Berrocal, 2017), nutrición (Burrows, Goldman, Pursey, & Lim, 2017), la actividad física (Álvarez-Bueno et al, 2017), el nivel socio-económico (Hair, Hanson, Wolfe, & Pollak, 2015), entre otros. En conclusión, la asociación entre el CASM-85 y el rendimiento académico no es fuerte, pero se encuentra dentro de un rango ISSN (Impreso): 1729-4827 ISSN (Digital): 2223-7666 Liberabit, 2019, 25(2), 139-158 (julio -diciembre) moderado considerando la naturaleza multifactorial de este último.…”
Section: Discussionunclassified